Optimisation and Characterisation of the Protein Hydrolysate of Scallops (Argopecten purpuratus) Visceral By-Products - Chasquibol Silva, Nancy Ascención (2023)
In this research, scallops (Argopecten purpuratus) visceral meal (SVM) and defatted meal (SVMD) were analysed for their proximal composition, protein solubility, and amino acid profile. Hydrolysed proteins isolated from the scallop’s viscera (SPH) were optimised and characterised using response surface methodology with a Box-Behnken design. The effects of three independent variables were examined: temperature (30–70 °C), time (40–80 min), and enzyme concentration (0.1–0.5 AU/g protein) on the degree of hydrolysis (DH %) as a response variable. The optimised protein hydrolysates were analysed for their proximal composition, yield, DH %, protein solubility, amino acid composition, and molecular profile. This research showed that defatted and isolation protein stages are not necessaries to obtain the hydrolysate protein. The conditions of the optimization process were 57 °C, 62 min and 0.38 AU/g protein. The amino acid composition showed a balanced profile since it conforms to the Food and Agriculture Organisation/World Health Organisation recommendations for healthy nutrition. The predominant amino acids were aspartic acid + asparagine, glutamic acid + Glutamate, Glycine, and Arginine. The protein hydrolysates’ yield and DH % were higher than 90% and close to 20%, respectively, with molecular weight between 1–5 kDa. The results indicate that the protein hydrolysates of scallops (Argopecten purpuratus) visceral by product optimised and characterised was suitable a lab-scale. Further research is necessary to study the bioactivity properties with biologic activity of these hydrolysates.